Aspects of Slavic linguistics : formal grammar, lexicon and communication - Mueller-Reichau, Olav; Guhl, Marcel (Language, context, and cognition ;, 2017)
The volume offers a selection of papers on current issues in Slavic languages. It takes stock of the past 20 years of research at the Department of Slavic Studies at Leipzig University. The papers tackle issues of all grammatical subdisciplines in current models of description, compare parts of the grammars of Slavic languages, and explain categories and phrases that do not exist in present-day Indogermanic languages of Western Europe.